Analysis of the Difficulties of Junior High School Students in Solving PISA Model Mathematics Problems - Hasibuan, Yenni Aprina; Hasanah, Rusi Ulfa (FKIP Universitas Lampung, 2022)
Analysis of the Difficulties of Junior High School Students in Solving PISA Model Mathematics Problems. Objectives: This study aimed to analyze the difficulties of students in working on PISA-model-math problems in Junior High School. Methods:The samples used in this qualitative research were 24 students of SMP Negeri 1 Padang Bolak class IX-A and 11 students of SMP Negeri 2 Padang Bolak class IX-B. The data collection technique used in this study was a written test of 6 essay questions that had been declared valid and reliable as well as interviews. Findings: Some of difficulties experienced by students were understanding the meaning of the problem, converting the problem into mathematical sentences, planning and implementing the problem solving, and logically concluding the problem’s solution. Conclusions: The mathematical ability to answer PISA at the level 1, 2, and 3 questions was good, while those for levels 4, 5, and 6 were still in the low category.Keywords: Student Difficulty analysis, PISA, Mathematics.DOI: http://dx.doi.org/10.23960/jpp.v12.i2.202204